The Discursive Construction of Child Molestation: A Critical Discourse Analysis of Transitivity in The Jakarta Post - Oktira, Harisa Dwi; Sinar, T. Silvana; Nurlela, Nurlela; Rangkuti, Rahmadyah (JOLLT Journal of Languages and Language Teaching, 2025)
This study employed Fairclough’s Critical Discourse Analysis, focusing on the discursive construction of child molestation using the transitivity process. The research aimed to (1) describe transitivity patterns in child molestation news articles published by The Jakarta Post, (2) examine how these patterns constructed the discourse, and (3) explore why such construction occurred. A qualitative content analysis was used to analyze clauses from five selected news texts. The study found that the most dominant transitivity processes were verbal and material. Verbal processes appeared 57 times (43.8%), while material processes occurred 48 times (36.9%), showing only a 6.9% difference. Verbal process verbs included reported, told, accused, said, and announced, while material process verbs included molested, abused, and arrested. These findings indicate that the news writers constructed the narratives based on information from police, witnesses, and victims to outline the chronology of the molestation incidents. The reports often portrayed children as the affected participants, with perpetrators positioned as the main actors responsible for the events. Through analyzing these transitivity patterns, the researcher identified how socio-cultural ideologies were embedded in the discourse. The texts implied that minors are perceived as vulnerable and lacking full legal protection. Moreover, the narratives challenged the common perception that women are always the victims of sexual abuse, showing that children of both genders could be victims. The perpetrators were often figures with authority in schools and the psychological impact on the victims was highlighted throughout the texts.